E-Government, Audit Opinion, and Performance of Local Government Administration in Indonesia - Bambang Sutopo; Trisninik Ratih Wulandari; Arum Kusumaningdyah Adiati; Dany Adi Saputra (Australasian Accounting, Business and Finance Journal, 2017)
Local governments (LGs) have an important role in providing services to the community. Nevertheless, some local governments still show relatively low performance. Scores of e-government implementation and audit opinions obtained by some local governments are also relatively low. This study examines whether there are relationships between e-government, the dimensions of e-government, and audit opinion and the performance of the local government administration. There are five dimensions of the e-government i.e. policy, institutions, infrastructure, applications, and planning. The sample used in this study includes 246 local governments from 2012 to 2014. Using regression analysis, the results of this study show that e-government has a positive association with the performance of the local government administration. This is supported by the positive association of e-government’s dimensions with performance. The audit opinion is also positively associated with performance as expected. These results suggest that e-government and audit opinion can be used as indicators of the performance of local government administration.
Keywords: e-government; audit opinion; performance; local government administration; Indonesia